Thrombin is a selective inducer of heparanase release from platelets and granulocytes via protease-activated receptor-1 - Tatour, Mifleh; Shapira, Ma'anit; Axelman, Elena; Ghanem, Shourouk; Keren-Politansky, Anat; Bonstein, Lilach; Brenner, Benjamin; Nadir, Yona (Thrombosis and Haemostasis, 2017)
Heparanase, known to be involved in angiogenesis and metastasis, was shown to form a complex with tissue factor (TF) and to enhance the generation of factor Xa. Platelets and granulocytes contain abundant amounts of heparanase that may enhance the coagulation system upon discharge. It was the aim of this study to identify the inducer and pathway of heparanase release from these cells. Platelets and granulocytes were purified from pooled normal plasma and were incubated with ATP, ADP, epinephrine, collagen, ristocetin, arachidonic acid, serotonin, LPS and thrombin. Heparanase levels were assessed by ELISA, heparanase procoagulant activity assay and western blot analysis. The effects of selective protease-activated receptor (PAR)-1 and 2 inhibitors and PAR-1 and 4 activators were studied. An in-house synthesised inhibitory peptide to heparanase was used to evaluate platelet heparanase involvement in activation of the coagulation system. Heparanase was released from platelets only by thrombin induction while other inducers exerted no such effect. The heparanase level in a platelet was found to be 40 % higher than in a granulocyte. Heparanase released from platelets or granulocytes increased factor Xa generation by three-fold. PAR-1 activation via ERK intracellular pathway was found to induce heparanase release. In conclusion, heparanase is selectively released from platelets and granulocytes by thrombin interacting with PAR-1. Heparanase derived from platelets and granulocytes is involved in activation of the extrinsic coagulation pathway. The present study implies on a potential anticoagulant effect, in addition to anti-platelet effect, of the new clinically studied PAR-1 inhibitors.
Keywords: Heparanase; thrombin; protease activated receptors (PAR); platelets; granulocytes